Prescription of antibiotics in bone augmentation with dental implant - Saleh Omar W.; Tawfeeq Bashar A.; Al-Rawee Rawaa Y. (Acta Marisiensis - Seria Medica)
Aim: To evaluate the success and failure in bone augmentation with dental implant cases when antibiotics were used with different timing in long follow-up periods.